Participatory Community Economic Development using Organic Agriculture in Nong Hee Subdistrict, Nong Hi District, Roi Et Province - Songkarin , Danaya; Pawala, Thanyachanok (Interdisciplinary Academic and Research Journal, 2022)
Participatory community economic development using organic agriculture in Nong Hee Subdistrict, Nong Hi District, Roi Et Province This qualitative research aims to study knowledge of agriculture from local farmers. To expand the results to the target farmers To develop a community economy with participation in organic farming for farmers in Nong Hi Subdistrict, Nong Hi District, Roi Et Province Collect data with in-depth document analysis In-depth interviews The researcher determined the total population of 103 people. The population was determined by random sampling, purposive sampling, and 3 target group size as follows: Providers of important data in semi-structured interviews. Community leaders Villagers 36 farmers representatives, 50 participants in the group discussion, consisting of community leaders And farmers representatives Model farmers in the operation of organic agriculture in the amount of 12 people. The research team within the community of 5 people, consisting of 3 farmers representatives, agricultural extension officers in the 2 people, including the survey of the farmers' plot area Informal talk Small group meeting Organizing a summary stage and reflecting the results of research with relevant agencies Analyze the data with content analysis and examine the data using the triangular technique. The results showed that the status, knowledge, and needs of Farmers have knowledge and expertise in the production process. Because through learning from various occupations and learning resources as well as being interested and active in the production and consumption of organic products Very much, but still lacking the correct understanding of organic agriculture according to the academic principles To enter the standard certification And the application of modern technology and technology in the production process Including lack of knowledge about farm management systems and marketing mechanisms To support the production of organic farming, it was found that the participation of development partners can push forward to drive the community at a sustainable level. The leading parties are villagers/farmers, the Department of Agriculture, local administrative organizations at all levels, and universities that teach agricultural education. Utilizing driving organic agriculture throughout the supply chain in 4 aspects: production factors, production and management, innovation and production technology, and production and management